2022
DOI: 10.2147/opth.s367756
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Extension Study Comparing Latanoprost 0.005% Without vs With Benzalkonium Chloride in Open-Angle Glaucoma or Ocular Hypertension

Abstract: Purpose To evaluate the long-term safety of latanoprost benzalkonium chloride (BAK)-free vs currently marketed latanoprost 0.005% ophthalmic solution containing BAK (referred to as reference), to treat open-angle glaucoma (OAG) or ocular hypertension (OHT). Patients and Methods This phase 3, multicenter, open-label, nonrandomized, single group assignment, safety study included patients who previously completed a phase 3 noninferiority study. Patients self-administered 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This study also demonstrated a mean ± SD IOP reduction in the study eye of 8.6 ± 2.6 mm Hg (~36%) at Day 84 (versus baseline) in the T2345 group and 9.0 ± 2.4 mm Hg (~38%) in the BPL group in the modified ITT (mITT) population. These findings are consistent with what has been reported in phase 3 clinical trials for BPL and potassium sorbatepreserved latanoprost 0.005%, 28 with reductions of 6-8 mm Hg from baseline for both, along with IOP reductions reported for other PGAs (~25%-33%). 29,30 An important difference between these clinical trials and the current trial is the baseline IOP levels.…”
supporting
confidence: 90%
“…This study also demonstrated a mean ± SD IOP reduction in the study eye of 8.6 ± 2.6 mm Hg (~36%) at Day 84 (versus baseline) in the T2345 group and 9.0 ± 2.4 mm Hg (~38%) in the BPL group in the modified ITT (mITT) population. These findings are consistent with what has been reported in phase 3 clinical trials for BPL and potassium sorbatepreserved latanoprost 0.005%, 28 with reductions of 6-8 mm Hg from baseline for both, along with IOP reductions reported for other PGAs (~25%-33%). 29,30 An important difference between these clinical trials and the current trial is the baseline IOP levels.…”
supporting
confidence: 90%
“…The same formulations were studied again in July 2022 by Lee et al The authors noted a similar hypotensive effect of the two formulations; however, BAK-containing latanoprost was slightly more effective in lowering IOP. The difference was not statistically significant, but the graph presented by the authors showed a higher decrease of IOP in patients using BAK-containing preparations [9]. In 2021, Skov et al published a meta-analysis that evaluated studies comparing the hypotensive effect of β-blocker timolol with and without preservatives.…”
Section: Efficacy Of Medicines Containing Preservativesmentioning
confidence: 95%
“…Similarly, authors of the second study reported more adverse effects in patients using BAK-free formulations (893 vs. 827). Therefore, it can be concluded that preservatives in ophthalmic drops do not affect their safety or the number of adverse effects [9]. In the meta-analysis, the level of evidence for all ocular surface outcomes was low or very low and reported in only a few studies.…”
Section: Adverse Effectsmentioning
confidence: 96%
See 1 more Smart Citation